The enhanced loyalty drivers of customers acquired through referral reward programs - Ramaseshan, Balasubramani; Wirtz, J.; Georgi, D. (Emerald Group Publishing, 2017)
Purpose: The purpose of this paper is to extend prior research on referral reward programs (RRPs) by examining if and how the mode of customer acquisition (RRP-acquired customers vs non-RRP-acquired new customers) moderates the relationships between customer satisfaction and attitudinal loyalty, perceived switching costs and attitudinal loyalty, and attitudinal loyalty and behavioral loyalty (i.e. recommendations, cross-buying, and total spend). Design/methodology/approach: Set in a banking context, this study is the first in an RRP context to link survey data with actual purchase data from a bank’s CRM records. Specifically, the survey captured customers’ satisfaction, perceived switching costs and attitudinal loyalty, whereas the CRM data provided actual loyalty behaviors (cross-buying and total spend). Findings: The findings show that the effect of satisfaction on attitudinal loyalty, and the effects of attitudinal loyalty on recommendations, cross-buying, and total spend were stronger for RRP-acquired customers than for non-RRP-acquired new customers. Furthermore, perceived switching costs had a lower effect on attitudinal loyalty for RRP-acquired customers than for non-RRP-acquired new customers. Practical implications: The findings offer managers a better understanding of how RRP-acquired customers differ from non-RRP-acquired new customers with regard to their satisfaction, perceived switching costs, and attitudinal and behavioral loyalty, thus enabling effective management of RRPs. Originality/value: This is the first empirical study that explores the differences between RRP-acquired customers and non-RRP-acquired new customers with regard to the effects of satisfaction and perceived switching costs on attitudinal loyalty, and the effect of attitudinal loyalty on behavioral loyalty.